2018
DOI: 10.1021/acs.iecr.7b03953
|View full text |Cite
|
Sign up to set email alerts
|

Acetone–Butanol–Ethanol Production from Fermentation of Hot-Water-Extracted Hemicellulose Hydrolysate of Pulping Woods

Abstract: In the kraft pulping process, the hemicellulose portion of wood is usually discharged as a waste stream into the black liquor, representing a highly underutilized sugar source. In this study, the hemicellulose prehydrolysate is investigated as a liquid sugar source for production of acetone, butanol, and ethanol by ABE fermentation. For this purpose, hot-water treatment is applied to poplar (hardwood) and southern pine (softwood) for hemicellulose extraction. The acquired hemicellulose prehydrolysate was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 29 publications
(112 reference statements)
0
27
0
Order By: Relevance
“…HWE conducted for only 1 h, under approximately the same conditions, yields lower mass removal than what is found in this present study. Guan et al found mass removal of 15.7% when HWE is performed on debarked hybrid poplar for 1 h at 170 • C (Guan et al, 2018). HWE of sugar maple removed 14.2% of the initial weight, when operated at 160 • C for 1 h (Mittal et al, 2009a).…”
Section: Mass Removed By Hot Water Extraction (Hwe) and Composition Omentioning
confidence: 99%
“…HWE conducted for only 1 h, under approximately the same conditions, yields lower mass removal than what is found in this present study. Guan et al found mass removal of 15.7% when HWE is performed on debarked hybrid poplar for 1 h at 170 • C (Guan et al, 2018). HWE of sugar maple removed 14.2% of the initial weight, when operated at 160 • C for 1 h (Mittal et al, 2009a).…”
Section: Mass Removed By Hot Water Extraction (Hwe) and Composition Omentioning
confidence: 99%
“…The integrated ‘biorefinery’ process to produce biofuels and chemicals as a supplementary unit in kraft paper mills is an intriguing possibility . Our previous research found that the production of various chemicals could be integrated into the kraft process, while still preserving the main products ‐ paper and pulp . However, the biggest bottleneck in this biorefinery process is the high cost of the enzymes for the hydrolysis step .…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 Acetone (C3) can be produced from the fermentation of glucose. 11,12 Combination of these components through aldol condensation allows the formation of products in the range of C8-C15 that could be further transformed in liquid alkanes in the fuel range through hydrogenation/dehydration/hydrodeoxygenation reactions. 13 Aldol condensation can be catalyzed by both acids and bases, being most commonly used base catalysts.…”
Section: Introductionmentioning
confidence: 99%